2008
DOI: 10.1159/000113502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Exercise and Food Restriction on the Biomechanical Properties of the Femur of Ageing Male Rats

Abstract: Background: Voluntary running in wheels as well as food reduction increase the life spans of rats. Disparate parameters such as the collagen biomarker of ageing and the development of kidney pathologies are decreased by voluntary exercise. There are few reports on the influence of physical exercise and food restriction on the skeleton of male rats. Most investigations initiated rather short-term interventions in 4- to 5-week-old animals and thus studied more the influence of growth than the influence of ageing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
6
1
Order By: Relevance
“…However, in accordance with our finding that trabecular BMD at the distal femoral and proximal tibial metaphyses declined precipitously between baseline and the end of the trial, axial compression tests of the distal femoral metaphysis showed a pronounced reduction in bone strength between 5 and 23 months of age in all groups [12] .…”
Section: Discussionsupporting
confidence: 91%
“…However, in accordance with our finding that trabecular BMD at the distal femoral and proximal tibial metaphyses declined precipitously between baseline and the end of the trial, axial compression tests of the distal femoral metaphysis showed a pronounced reduction in bone strength between 5 and 23 months of age in all groups [12] .…”
Section: Discussionsupporting
confidence: 91%
“…17 Not only are the effects of calorie restriction opposite to those of sleep restriction with regard to vital organ masses, but mild calorie restriction alone has been shown to have a beneficial effect on metaphyseal strength, as determined in sedentary, aging rats. 18 Comparisons of the sleep-deprived state with other examples of hypermetabolism also do not provide enough similarities to conclude that energy expenditure during sleep restriction has only a unidirectional effect of on bone formation. For example, hypermetabolism induced by thyroid hormone administration results not only in increased osteoclast surface areas and bone loss, but in increased osteoid and osteoblast surface areas.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed that rat bone strength increases with age up to 1 yr of age, after which there is a slow reduction in strength as the animal ages (Fukuda and Iida 2004;Thomsen et al 2008). Similarly, human bone strength decreases with age, and this fall is more pronounced than in rats (Mueller et al 2009).…”
Section: Discussionmentioning
confidence: 99%